KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU PADA SD NEGERI 13 KOTA BANDA ACEH - Khatijah .; Murniati AR; Niswanto . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
The principal is the person responsible for improving the professional competence of teachers in the school. The purpose of this research is looking at program arrangement, program implementation, and obstacles encountered. The research methodology used in this study was qualitative technique, and for data collection was done by way of documentation, observation and interview. The sources of data in this study were gathered from the principal and teachers. The result of this study showed that the programs used by the principal in improving the professional competence of teachers were to require the teachers to make RPP, syllabus, annual program, and prepare the teaching materials before the learning and teaching process implemented. There are two strategies used in improving the professional competence of teachers: Formal and Non Formal. Formal strategy were including teacher training, professional training, seminars, while the Non-Formal strategy were emphasizing discipline and motivating teachers. The obstacles faced by the head of SD Negeri 13 Banda Aceh were the lack of teachers and even some existing teachers did not master the IT, and the limited time obtained by teachers at the time following the training and so forth.